Identifikasi Kandungan Senyawa Metabolit Sekunder pada Daun Jambu Biji (Psidium Guajava L Var. Pyrifera) di Kabupaten Bandung - Habib Indraswara; Nadya Nur Aisyah; Rini Rini; Muhimatul Umami (International Forum of Researchers and Lecturers, 2024)
Secondary metabolites are compounds produced by plants, microorganisms and animals through the process of biosynthesis or derivatives from primary metabolites. The maceration method is a simple way to separate bioactive compounds from plant material. Guava leaves contain secondary metabolite compounds which have medicinal effects such as antibacterial, antioxidant and anti-inflammatory. This simplicia leaf is soaked in 96% ethanol (using the maceration method) for 24 hours and concentrated using a rotary evaporator. Alkaloid, flavonoid and saponin tests show that guava leaves contain these three compounds. These compounds have potential for development in the pharmaceutical field.